Molecular Pathophysiology of Epithelial Barrier Dysfunction in Inflammatory Bowel Diseases - Jessica Y. Lee; Valerie C. Wasinger; Yunki Y. Yau; Emil Chuang; Vijay Yajnik; Rupert WL. Leong (Proteomes, 2018)
Over the years, the scientific community has explored myriads of theories in search of the etiology and a cure for inflammatory bowel disease (IBD). The cumulative evidence has pointed to the key role of the intestinal barrier and the breakdown of these mechanisms in IBD. More and more scientists and clinicians are embracing the concept of the impaired intestinal epithelial barrier and its role in the pathogenesis and natural history of IBD. However, we are missing a key tool that bridges these scientific insights to clinical practice. Our goal is to overcome the limitations in understanding the molecular physiology of intestinal barrier function and develop a clinical tool to assess and quantify it. This review article explores the proteins in the intestinal tissue that are pivotal in regulating intestinal permeability. Understanding the molecular pathophysiology of impaired intestinal barrier function in IBD may lead to the development of a biochemical method of assessing intestinal tissue integrity which will have a significant impact on the development of novel therapies targeting the intestinal mucosa.